Influence of the Finite Size Effect on Properties of a Weakly Interacting Bose G as in Improved Hatree-fock Approximation - Thu, Nguyen Van; Thi Theu, Luong (VNU Journal of Science: Mathematics - Physics, 2018)
The finite size effect causes many interesting behaviors in properties of a weakly interacting Bose gas. These behaviors were considered in one-loop approximation of quantum field theory. In this paper the influence is investigated in improved Hatree-Fock approximation, which gives more accurate results.